2022
DOI: 10.3389/fneur.2021.787161
|View full text |Cite
|
Sign up to set email alerts
|

Team Prenotification Reduces Procedure Times for Patients With Acute Ischemic Stroke Due to Large Vessel Occlusion Who Are Transferred for Endovascular Therapy

Abstract: Background: The clinical benefit from endovascular therapy (EVT) for patients with acute ischemic stroke is time-dependent. We tested the hypothesis that team prenotification results in faster procedure times prior to initiation of EVT.Methods: We analyzed data from our prospective database (01/2016–02/2018) including all patients with acute ischemic stroke who were evaluated for EVT at our comprehensive stroke center. We established a standardized algorithm (EVT-Call) in 06/2017 to prenotify team members (int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The advantages of the prenotification, announcing the approximate arrival of the patient at the CSC to optimize workflow through the direct availability of stroke neurologists, neuro-interventionalists and anesthesiologists, as well as the CT scanner, for the management in the CSC have been discussed in detail in a previous study [ 11 ]. Based on the current results, we found that there is further potential for optimization, especially during on-call periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the prenotification, announcing the approximate arrival of the patient at the CSC to optimize workflow through the direct availability of stroke neurologists, neuro-interventionalists and anesthesiologists, as well as the CT scanner, for the management in the CSC have been discussed in detail in a previous study [ 11 ]. Based on the current results, we found that there is further potential for optimization, especially during on-call periods.…”
Section: Discussionmentioning
confidence: 99%
“…Neuro-interventionalists were on-call on weekdays between 4:00 p.m. and 7:00 a.m., on weekends, and holidays. In June 2017, we implemented a team prenotification call, announcing the approximate arrival of the patient at the CSC to optimize workflow through the direct availability of stroke neurologists, neuro-interventionalists and anesthesiologists, as well as the CT scanner [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…1 An early index of suspicion and an optimized diagnostic and treatment workflow is important. 3 4 EVT comprises the use of a device or occasionally intra-arterial pharmacological therapy to recanalize an occluded artery. Across multiple randomized clinical trials in the early and late window, recanalization has been proven to improve functional outcomes.…”
mentioning
confidence: 99%